Use of Acoustic Telemetry to Identify Spawning River and Spawning Migration Patterns of American Shad in the Albemarle Sound, North Carolina. (31st January 2021) - Mack, Kevin; White, Holly; Rohde, Fred C.
Abstract: American Shad Alosa sapidissima is an economically, culturally, and ecologically important anadromous species that undertakes a significant spawning migration, swimming from the ocean into areas far upstream in coastal rivers to reproduce. The species has a large range in the western Atlantic, occurring from Nova Scotia to Florida. However, because American Shad generally return to their natal rivers to spawn, each major river likely has its own spawning stock. Fish that are entering the Albemarle Sound, North Carolina, to spawn primarily ascend one of two rivers at the far western end of the estuary: the Roanoke River or the Chowan River. Determining the current primary spawning river for American Shad in the Albemarle Sound would help inform research efforts and resource management decisions to improve stocks. American Shad were captured in the Albemarle Sound, tagged with sonic transmitters, and tracked using an array of acoustic receivers. Of the 62 fish that made detectable migrations during the six study years, 55 ascended the Chowan River, while only 5 ascended the Roanoke River and 2 entered other rivers. These telemetry results suggest that the Chowan River and its tributaries are the major spawning rivers for American Shad in the Albemarle Sound.